MANAGEMENT PROFILE OF GUIDANCE AND COUNSELING IN JUNIOR HIGH SCHOOL - Ratnawulan, Teti; Aulia Rahman, Sidiq (PEOPLE: International Journal of Social Sciences, 2017)
Need analysis is required in school management, so is in guidance and counseling management. Planning is as well needed in conducting guidance and counseling (G&C) program for all cities and regencies of Bandung. The applied research method was Research & Development. The data were obtained by using documents, questionnaires, and interviews. The results show that there are still G&C personnel with irrelevant educational background, and have not fulfilled the quota. In supporting services, it is required G&C facilities and infrastructures (accessible room). G&C instruments already exist including data storage tool, but for the city of Bandung has not yet fulfilled its data completion tool.